Aspects of Love in Shakespeare's Early Plays - Tóth Szilvia (2008)
This thesis examines three of Shakespeare's early plays (A Midsummer Night's Dream, Romeo and Juliet and The Taming of the Shrew) from the point of view of different aspects of love presented in them. I will examine and compare the love types that appear in each play. I will prove that Shakespeare adjusted to the popular taste and kept in mind the events of his age, but he also included new thoughts into his works already in his early period that is thought not to be as mature as the later periods. In order to prove my thesis, I will first write about the popular taste of the Elizabethan audience and reading public. Then, I will analyse A Midsummer Night's Dream and Romeo and Juliet. These two plays have many common features in terms of love. As opposed to these plays, I will also analyse The Taming of the Shrew. There are many critical debates and approaches concerning this play, and it presents quite different aspects of love, for example, the life of a couple after the marriage. As a conclusion I will show that Shakespeare, while writing his early plays, kept in mind the popular taste of his audience, however, he was ahead of his time by presenting love from many different aspects.